2021
DOI: 10.1186/s40104-020-00536-0
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of natural products capable of inducing porcine host defense peptide gene expression using cell-based high throughput screening

Abstract: Background In-feed antibiotics are being phased out in livestock production worldwide. Alternatives to antibiotics are urgently needed to maintain animal health and production performance. Host defense peptides (HDPs) are known for their broad-spectrum antimicrobial and immunomodulatory capabilities. Enhancing the synthesis of endogenous HDPs represents a promising antibiotic alternative strategy to disease control and prevention. Methods To identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Maintenance of a histone hyperacetylation and hypomethylation status of target gene promoters largely contributes to transcript expression ( 16 , 17 ). Several nutrients and natural products upregulate HDP expression through histone modification ( 7 , 13 ). However, whether deoxyshikonin induces the expression of porcine HDP genes and other immunoregulatory genes through this way requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of a histone hyperacetylation and hypomethylation status of target gene promoters largely contributes to transcript expression ( 16 , 17 ). Several nutrients and natural products upregulate HDP expression through histone modification ( 7 , 13 ). However, whether deoxyshikonin induces the expression of porcine HDP genes and other immunoregulatory genes through this way requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Deoxyshikonin, an active component of Lithospermum erythrorhizon , is a promising drug candidate for the treatment of wounds and cancers ( 5 , 6 ). In a screening of a library of 1,261 natural compounds using a newly established IPEC-J2/ pBD3 -luc cell line, we previously found that deoxyshikonin induces the expression of porcine host defense peptides (HDPs) ( 7 ). In addition, deoxyshikonin had a minimal effect on the expression of several representative inflammatory cytokine genes and obviously enhanced the antibacterial activity of 3D4/31 macrophages against both gram-negative and gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…HTC/ AvBD10-luc cell clone D5 were seeded at 2 × 10 4 cells/well in 50 μL of complete RPMI 1640 medium in 96-well plates overnight prior to exposure to 20 µM of each of the 148 compounds in an Epigenetics Screening Library (Cayman Chemical) in individual wells for 24 h prior to luciferase assay. To assess potential cytotoxicity of each compound, an alamarBlue dye (Thermo Fisher Scientific) was added to a final concentration of 10% and incubated for 4 h as we previously described [ 23 , 37 , 50 ]. Cytotoxicity was assessed in live cells by measuring the fluorescence at 545 nm excitation and 590 nm emission on Fx80 Microplate Fluorescence Reader (BioTek Instruments, Winooski, VT, USA), followed by luciferase assay on L-Max II Luminescence Microplate Reader (Molecular Devices) using Steady-Glo ® Luciferase Assay System (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity was assessed in live cells by measuring the fluorescence at 545 nm excitation and 590 nm emission on Fx80 Microplate Fluorescence Reader (BioTek Instruments, Winooski, VT, USA), followed by luciferase assay on L-Max II Luminescence Microplate Reader (Molecular Devices) using Steady-Glo ® Luciferase Assay System (Promega). The relative luciferase activity was normalized to the cell viability for each compound as we described [ 23 , 37 , 50 ]. To select hits, strictly standardized mean difference (SSMD) values were subsequently calculated as , where μ s and μ n are the mean luciferase activity of positive and negative controls, respectively, while σ is the standard deviation of the negative control [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…A high-throughput screening (HTS) assay based on a stable LL-37 promoter-driven luciferase reporter cell line (MN8CampLuc), has been developed and has led to the identification of multiple LL-37 inducers [ 22 , 23 ]. We also established different luciferase reporter cell lines through the stable integration of HDP promoter-driven luciferase reporter genes in macrophages or intestinal epithelial cell lines [ 24 , 25 ], which were subsequently employed to identify a number of HDP-inducing compounds [ 24 , 25 , 26 , 27 ]. Here, we report a large-scale screening of 5002 natural and synthetic small-molecule compounds with much greater structural and functional diversities using one such reporter cell line, termed HTC/ AvBD9-luc [ 25 ].…”
Section: Introductionmentioning
confidence: 99%